A Study of a Magnetic Cloud Propagating Through Large‐Amplitude Alfvén Waves. Issue 6 (13th June 2020) - Farrugia, C. J.; Lugaz, N.; Vasquez, B. J.; Wilson, L. B.; Yu, W.; Paulson, K.; Torbert, R. B.; Gratton, F. T.
Abstract: We discuss Wind observations of a long and slow magnetic cloud (MC) propagating through large‐amplitude Alfvén waves (LAAWs). The MC axis has a strong component along GSE X, as also confirmed by a Grad‐Shafranov reconstruction. It is overtaking the solar wind at a speed roughly equal to the upstream Alfvén speed, leading to a weak shock wave 17 hr ahead. We give evidence to show that the nominal sheath region is populated by LAAWs: (i) a well‐defined de Hoffmann‐Teller frame in which there is excellent correlation between the field and flow vectors, (ii) constant field and total pressure, and (iii) an Alfvén ratio (i.e., ratio of kinetic‐to‐magnetic energy of the fluctuations) near unity at frequencies much lower than the ion cyclotron frequency in the spacecraft frame. In the region where the LAAWs approach the MC's front boundary there are field and flow discontinuities. At the first, magnetic reconnection is taking place, as deduced from a stress balance test (Walén test). This severs connection of some field lines to the Sun and the solar wind strahl disappears. There follows a 2‐hr interval where the magnetic field strength is diminished while pressure balance is maintained. Here the bidirectionality of the suprathermal electron flows is intermittently disrupted. This interval ends with a slow expansion fan downstream of which there is a dropout of halo electrons just inside the front boundary of the MC. This study illustrates an untypical case of a slow MC interacting with LAAWs in the slow solar wind. Key Points: Large‐amplitude Alfvén waves are reported in the sheath of a magnetic cloud Reconnection at a discontinuity in the cloud sheath is followed by a slow expansion fan Magnetic cloud has an untypical orientation and is not force free